ChemInform Abstract: Facile Baeyer—Villiger Oxidation of Cyclic Ketones: Conventional versus Microwave‐Assisted Approach. Issue 7 (January 2016) - Randino, Rosario; Cini, Elena; D'Ursi, Anna Maria; Novellino, Ettore; Rodriquez, Manuela
Abstract: This microwave‐assisted oxidation procedure significantly reduces the reaction time compared to conventional conditions (room temperature, 5 days) and provides the target lactones in excellent yields.